2022
DOI: 10.3390/s22145067
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy Associated with the Design of Experiments and Machine Learning for Discrimination of Brachiaria brizantha Seed Vigor

Abstract: Laser-induced breakdown spectroscopy (LIBS) associated with machine learning algorithms (ML) was used to evaluate the Brachiaria seed physiological quality by discriminating the high and low vigor seeds. A 23 factorial design was used to optimize the LIBS experimental parameters for spectral analysis. A total of 120 samples from two distinct cultivars of Brachiaria brizantha seeds exhibiting high vigor (HV) and low vigor (LV) in standard tests were studied. The raw LIBS spectra were normalized and submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Recent research in the literature has explored various computational methods that correlate image-derived parameters with seed quality standards [5,10,11]. Image analysis techniques provide non-destructive means to comprehend various aspects of seed development, establishing a connection between internal morphology and structural integrity [8,[12][13][14]. This approach enables the determination of the physiological potential of seed lots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in the literature has explored various computational methods that correlate image-derived parameters with seed quality standards [5,10,11]. Image analysis techniques provide non-destructive means to comprehend various aspects of seed development, establishing a connection between internal morphology and structural integrity [8,[12][13][14]. This approach enables the determination of the physiological potential of seed lots.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [7] combined low-field nuclear magnetic resonance (LF-NMR) spectral data and machine learning algorithms like Fisher's linear discriminant (FLD) to accurately distinguish high-and low-vigor rice seeds. Cioccia et al [12] used laser-induced breakdown spectroscopy (LIBS) and machine learning algorithms like linear discriminant analysis (LDA) to evaluate the vigor of Brachiaria brizantha seeds, achieving 100% accuracy in distinguishing high-and low-vigor seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In the research that focused on the identification of seed vigor of soybean and Brachiaria using LIBS, it was found that the presence of Ca elements in the seeds is the main characteristic responsible for the major variance in the data. Therefore, due to the fact that Ca elements play an important role in enzyme activities of plant during germination, LIBS was able to determine the seed vigor of soybean [26] and Brachiaria [27] by identifying Ca elements.…”
Section: Introductionmentioning
confidence: 99%